2017
DOI: 10.1186/s12889-017-4937-9
|View full text |Cite
|
Sign up to set email alerts
|

Health and healthcare disparities among U.S. women and men at the intersection of sexual orientation and race/ethnicity: a nationally representative cross-sectional study

Abstract: BackgroundResearch has shown that sexual minorities (SMs) (e.g. lesbian, gay, and bisexual individuals), compared to their heterosexual counterparts, may engage in riskier health behaviors, are at higher risk of some adverse health outcomes, and are more likely to experience reduced health care access and utilization. However, few studies have examined how the interplay between race and sexual orientation impacts a range of health measures in a nationally representative sample of the U.S. population.MethodsTo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 32 publications
3
84
0
1
Order By: Relevance
“…Second, there was no heterosexual comparison group, which would have provided a more thorough picture of how intersecting racial/ethnic and sexual identities may be differentially associated with depression and victimization. Newer work based on the National Health Interview Survey (Trinh, Agénor, Austin, & Jackson, 2017) demonstrated that White, Black, and Latina SMW each had higher odds of reporting that they felt “depressed” in the last week than their heterosexual counterparts. However, when compared to White heterosexual women, only White and Black SMW women had higher odds of weekly feelings of depression, whereas Latina SMW did not differ from White heterosexual women.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there was no heterosexual comparison group, which would have provided a more thorough picture of how intersecting racial/ethnic and sexual identities may be differentially associated with depression and victimization. Newer work based on the National Health Interview Survey (Trinh, Agénor, Austin, & Jackson, 2017) demonstrated that White, Black, and Latina SMW each had higher odds of reporting that they felt “depressed” in the last week than their heterosexual counterparts. However, when compared to White heterosexual women, only White and Black SMW women had higher odds of weekly feelings of depression, whereas Latina SMW did not differ from White heterosexual women.…”
Section: Discussionmentioning
confidence: 99%
“…This scholarship that challenges SGM identity measurement is important in order to improve our understanding of health disparities experienced by sexual and gender minorities, and to provide culturally responsive health care in clinical settings. After all, scholars have noted distinct disparities for ethnoracial SGM youth compared to their White SGM counterparts in BMI (Katz‐Wise et al., ), and a host of other health‐related outcomes such as risk of stroke, cancer, drinking and sleep problems, and obesity (Trinh, Agénor, Austin, & Jackson, ). Lacking in the extant literature is a full consideration of emerging identity labels among youth.…”
Section: Ethnoracial Sexual and Gender Identities In An Adolescent mentioning
confidence: 99%
“…There are likely a variety of factors influencing this growth, such as the increasing visibility in popular culture of individuals that are neither hetero- nor homosexual (e.g., pop stars and television show characters), which may increase the social acceptability of bisexual identity (Callis, 2014). The elevated smoking rates among sexual minorities coupled with lower access to healthcare (Trinh et al, 2017) lead to an increased risk for negative health consequences (e.g., cancer, respiratory illnesses, cardiovascular diseases) (Blosnich et al, 2013; Caceres et al, 2017). Moreover, tobacco use disparities among sexual minority individuals are likely established in smoking initiation during adolescence and young adulthood (Burkhalter, 2015; Corliss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%